Outcomes in Juvenile-Onset Spondyloarthritis - Smith, Judith A.; Burgos-Vargas, Ruben (Frontiers in Medicine, 2021)
Some studies have suggested children with juvenile onset spondyloarthritis (JoSpA) have a relatively poor outcome compared to other juvenile idiopathic arthritis (JIA) categories, in regards to functional status and failure to attain remission. Thus, in the interest of earlier recognition and risk stratification, awareness of the unique characteristics of this group is critical. Herein, we review the clinical burden of disease, prognostic indicators and outcomes in JoSpA. Of note, although children exhibit less axial disease at onset compared to adults with spondyloarthritis (SpA), 34-62% have magnetic resonance imaging (MRI) evidence for active inflammation in the absence of reported back pain. Furthermore, some studies have reported that more than half of children with “enthesitis related arthritis” (ERA) develop axial disease within 5 years of diagnosis. Axial disease, and more specifically sacroiliitis, portends continued active disease. The advent of TNF inhibitors has promised to be a “game changer”, given their relatively high efficacy for enthesitis and axial disease. However, the real world experience in various cohorts since the introduction of more widespread TNF inhibitor usage, in which greater than a third still have persistently active disease, suggests there is still work to be done in developing new therapies and improving the outlook for JoSpA.